THE EFFECT OF KIDS’ IMAGINATION AND INSPIRATION FLIP (KIDIFLIP) MEDIA ON STORYTELLING INTEREST OF 5-YEAR-OLD CHILDREN AT TK KEMALA BHAYANGKARI 33 UNGARAN - Nur Azizah; Swantyka Ilham Prahesti; Himmah Taulany; Ari Pardi (Department of Early Childhood Education, Universitas Bina Bangsa Getsempena, 2026)
Storytelling interest is an essential aspect of early childhood language development; however, in practice, many children show low interest in expressing stories orally. This condition was observed among five-year-old children at TK Kemala Bhayangkari 33 Ungaran, who demonstrated limited confidence, attention, and ability to convey story sequences. This study aimed to examine the effect of using the Kids’ Imagination and Inspiration Flip (KidiFlip) media on the storytelling interest of five-year-old children. The study employed a quantitative approach with a one-group pre-test and post-test design. The sample consisted of 25 children selected through purposive sampling. Data were collected using observation sheets and storytelling interest questionnaires with a 1–5 rating scale, then analyzed using the Shapiro–Wilk normality test, Levene’s homogeneity test, and the paired sample t-test. The results showed an increase in the mean storytelling interest score from 24.4 in the pre-test to 46.4 in the post-test. The paired sample t-test revealed a significance value of 0.000 < 0.05, indicating a significant effect of the KidiFlip media on children’s storytelling interest. The KidiFlip media proved effective in improving children’s attention, confidence, and participation in storytelling activities in early childhood education.